Empowering Cadres in the Practice of Infant and Child Feeding Improve Nutritional Status of Children - Ratnawati, Ratnawati; Utami, Riana Pangestu; Novaria, Astri Ayu (Universitas Serang Raya, 2025)
Community-based interventions are necessary to reduce the number of children under five who experience weight faltering, underweight, and wasting in the Mesjid subdistrict of Samarinda City to prevent them from developing stunting. This activity aimed to train health cadres in Infant and Young Child Feeding (IYCF) and provide supplementary food based on local foods to children under five with nutritional problems. The activity was conducted in two stages: the first was IYCF training for cadres with a total of 63 participants, and the second was providing supplementary food to 28 target children. The activities were evaluated using knowledge questionnaires for the cadres and weight measurements after one week of supplementary feeding interventions and IYCF education for the children. The results of the community service showed an increase in cadre knowledge related to IYCF, with the majority previously in the poor category (60.3%) improving to a majority in the adequate category (65.1%) after the training. There was also an increase in the weight of children who received local food-based supplementary feeding, with the average weight increasing from 10.15 kg in the pretest to 10.54 kg in the posttest. This activity proved beneficial in improving the knowledge of cadres and the weight of children, and it is hoped that the subdistrict, health centers, and cadres will commit to being responsible for monitoring and evaluating the sustainability of the activities.